Risk factors for pulmonary mucormycosis in subjects with diabetes mellitus—A case‐control study - Garg, Deepak; Soundappan, Kathirvel; Agarwal, Ritesh; Mukherjee, Soham; Kumar, Mahendra; Dhooria, Sahajal; Sehgal, Inderpaul Singh; Prasad, Kuruswamy Thurai; Ramachandran, Raja; Patil, Shivakumar; Aggarwal, Ashutosh Nath; Rudramurthy, Shivaprakash Mandya; et al. (Mycoses, 2023)
Background Factors associated with pulmonary mucormycosis (PM) among subjects with diabetes mellitus (DM) remain unclear. Following the coronavirus disease (COVID‐19)‐associated mucormycosis outbreak in India, specific environmental exposures (especially cattle dung exposure) were proposed as possible aetiology. We hypothesized that environmental factors are associated with PM. We compared subjects with DM with (cases) and without PM (controls). Methods In this case‐control study, for each PM case, we included five unmatched diabetic controls (hospital [n = 2], community [n = 3]) without PM. We collected information on demography, COVID‐19 infection, glycated haemoglobin% (HbA1c), the type of house (pucca vs. kutcha) where the participants reside, and other environmental factors. The primary exposure tested was cattle dung exposure (CDE; using cattle dung cakes as fuel or cattle handling). We performed a multivariate logistic regression to explore factors associated with PM and report the association as an adjusted odds ratio (OR) with 95% confidence intervals (CI). Results We enrolled 39 PM cases and 199 controls (hospital [n = 80], community [n = 119]). CDE (OR 0.68, 95% CI [0.14‐3.31]; p = 0.63) was not associated with increased PM in DM. We found male sex (OR 4.07, 95% CI [1.16‐14.31]), higher HbA1c (OR 1.51, 95% CI [1.18‐16.32]), COVID‐19 (OR 28.25, 95% CI [7.02‐113.6]) and residence at kutcha house (OR 4.84, 95% CI [1.33‐17.52]) associated with PM. Conclusion Cattle dung exposure was not associated with PM in subjects with DM. Instead, male sex, poor glycaemic control, COVID‐19 and the type of housing were associated with pulmonary mucormycosis.